A review on long-term electrical power system modeling with energy storage. (20th January 2021) - Lai, Chun Sing; Locatelli, Giorgio; Pimm, Andrew; Wu, Xiaomei; Lai, Loi Lei
Abstract: Driven by the demand for intermittent power generation, Energy Storage (ES) will be widely adopted in future electricity grids to provide flexibility and resilience. Technically, there are two classes of ES for storing low-carbon energy: Generation-Integrated Energy Storage (GIES) and non-GIES. GIES stores energy along with the transformation between the primary energy form (e.g., thermal energy) and electricity. Long-term Electrical Power System Models (LEPSMs) support analysis including decarbonization studies and energy technology assessments. Current LEPSMs are limited in describing the power system with ES (e.g., considering one type of ES and not considering GIES). Consequently, a novel LEPSM is needed, and this paper paves the way towards this goal by bringing together the literature on ES and LEPSMs. This paper provides a state-of-the-art review of LEPSMs and shows that (a) existing models are inadequate to address grids with a high percentage of renewables and ES; and (b) there is a challenge in integrating short-term temporal changes in LEPSMs due to model complexity and computational cost. Finally, this paper proposes a framework for long-term electrical power system modeling considering ES and low-carbon power generation, which we have named the long-term power flow electrical power system framework. The key features of this novel framework are its agent-based modeling of consumer behavior, scenario reduction for renewables, and power flow analysis. Highlights: Comprehensive review of Long-term Electrical Power System (LEPS) models. LEPS models need to account for different energy storage technologies. A framework is proposed for LEPS modeling considering energy storage. Exploring Generation-Integrated Energy Storage in electrical power systems. Energy storage techno-economic studies can be enhanced with the proposed framework.